The liar's dictionary : a novel - Williams, Eley (William Heinemann, 2020)
"Peter Winceworth, a disaffected Victorian lexicographer, inserts false entries into a dictionary- violating and subverting the dictionary's authority- in an attempt to assert some sense of individual purpose and artistic freedom. In the present day, Mallory, a young overworked and underpaid intern employed by the dictionary's publishing house, is tasked with uncovering these entries before the work is digitised. As the novel progresses and their narratives combine, as Winceworth imagines who will find his fictional words in an unknown future and Mallory discovers more about the anonymous lexicographer's life through the clues left in his fictitious entries, both discover how they might negotiate the complexities of an absurd, relentless, untrustworthy, hoax-strewn, undefinable life. Braiding together contemporary and historical narratives, the novel explores themes of trust, agency and creativity, celebrating the rigidity, fragility and absurdity of language."--Provided by publisher.